Contributing Factors for Placenta Accreta in Patients Presenting in a Tertiary Care Hospital - Samina Ashraf, Shabana Rafique, Razia Bibi, Sara Munir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: determine the frequency of contributing factors for placenta accreta in patients presenting in a tertiary care hospital Methodology: The study was conducted on all the pregnant patients diagnosed with placenta preavia on ultrasound that were admitted through emergency and outpatient department of Lady Willingdon Hospital Lahore. A total of 180 patients fulfilling the inclusion/exclusion criteria coming to the Emergency Department were recruited in study. Contributing risk factors i.e. placenta previa, number of previous caesarean sections, and Dilatation & Curettage were recorded by the researcher herself on a pre-designed proforma attached. Data was collected and analyzed by single researcher to overcome the bias. Results: In our study, out of 180 cases, 73.33%(n=132) were between 20-30 years of age while 26.67%(n=48) had >30 years of age, mean+sd was calcualted as 27.89+4.14 years, 73.33%(n=132) were between 20-30 years of age while 26.67%(n=48) had >30 years of age, mean+sd was calcualted as 27.89+4.14 years, contributing factors of placenta accreta shows that 87.22%(n=157) had placenta previa, 51.67%(n=93) had <2preivous cesarean section, 48.33%(n=87) had 3 previous cesarean section and 27.22%(n=49) had D&C. Conclusion: We concluded that Placenta previa is a leading contributing factor followed by 2 and 3 cesarean sections and D&C for placenta accreta. Keywords: Placenta accreta, contributing factors, placenta previa, previous cesarean section, dialatation & curettage